THE CORRELATION BETWEEN STUDENTS' SELF-CONFIDENCE AND THEIR SPEAKING SKILLS - Selerang, Erika; Liando, Nihta; Andries, Fivy (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The aim of this research intends to find out whether there is significant correlation between students’ self-confidence and their speaking skills or not. This study was conducted at SMK Negeri 2 Tondano. The subject of this study consisted of 30 students. The data of the sample were obtained from questionnaires and data of speaking skills taken from mid test scores speak English of the first semester. The data of this study were analyzed statistically with Pearson Product Moment Correlation. The findings show that there is a high relationship correlation between students’ self-confidence and their speaking skills. This was shown by the correlation of rxy= 0.632. this correlation was significant and greater than 0.374 at the 0.05 level of significant. Based on the result it can be conclusion that students’ self-confidence is very strongly correlates with students’ speaking skills. The suggestions of this research is the teacher should more often provide material that can involve students’ in the classroom, so they can participate in learning and not feel bored and teacher has to be more creative in the teaching and learning process.